Fluid flow and solute dilution in laser linear butt joining of 304SS and Ni. (November 2020) - Li, Zhiyong; Yu, Gang; He, Xiuli; Li, Shaoxia; Li, Zixun
Highlights: Study of solidification phenomenon for laser dissimilar welding in 3D view. Spatial and directional characteristics for convection flow and concentration dilution. Dilution is largely affected by welding speed, TCST and dynamic viscosity. Mixing for spot welding is generally more uniform compared with linear welding. Abstract: Laser linear welding combined with advanced auto-control technology is a promising joint method of dissimilar metals. In this study, an improved three-dimensional model was developed to investigate the thermal behavior, fluid flow and concentration dilution during laser linear dissimilar welding of 304 stainless steel and nickel. The fluid flow and solidification behavior were presented in a 3D view to deeply study the thermal behavior and convection characteristics inside the melt pool. The relationship between dynamic characteristics and concentration dilution was studied numerically and experimentally, and the effects of welding speed, temperature coefficient of surface tension (TCST) and dynamic viscosity on mass transfer were also investigated. Larger cooling rate (GR) and smaller morphology parameter (G/R) were found at top area of the weld pool (WP). Elements from SS (Cr and Fe) were mainly mixed at front side, but Ni was mainly diluted at middle part. Resulting from the Marangoni convection, all the elements were mainly mixed at top area and then transported to the bottom. The redistribution of the species was also observed at each side, resulting in a relatively uniform distribution at each side. Nevertheless, the effects of welding speed, TCST and dynamic viscosity on solute dilution were simulated and proved non-negligible. Differences of solidification and dilution phenomenon were also observed between liner welding and spot welding. It was demonstrated the obtained results in this work provided a vital perspective in comprehending the heat and mass transfer phenomenon inside the melt pool during welding and additive manufacturing process.